DEVELOPMENT OF POP UP BOOK LEARNING MEDIA AT THE FIVE GRADE IPA CONTENT OF WONOKERTO STATE ELEMENTARY SCHOOL - Mei Lanti; Haromoko Harmoko; Asep Sugenda Egok (xxxx-xxxx, 2022)
This research aims to develop teaching media products in the form of pop up book learning media. On the content of science class V SD Negeri Wonokerto which is valid, practical and effective for use in the learning process. The research method is RD (Research and development), with the ADDIE development model used analysis, design, development, implementation and evaluation. Based on the results of the analysis of assessments obtained from language validation experts, the average score of 0.87 is included in the high category, material experts have an average score of 0.84 in the high category and media experts have an average score of 0.77 including the fairly high category. Then the results of the practical analysis of students obtained an average of 92% for small groups very practical criteria, and large groups scored 97% very practical criteria and teacher practicality scored 94% very practical criteria. The quality of the pop up book media seen from the practical aspect is categorized as very practical with an overall score of 94% being very practical. Then the results of the effectiveness analysis obtained an average pretest score of 21.2 and a posttest score of 73.8 and the classical learning completeness criteria obtained a score of 66.7% including the "Good" category.